Recurrent fever of unknown fungal infection in a low-risk patient: A case report. Issue 33 (August 2019) - Guo, Tang-meng; Ye, Yu; Huang, Li-li; Cheng, Bei
Abstract: Rationale: Fungal infectious disease does not usually occur in low-risk patients. Clinicians tend to ignore the role of fungi in the fevers of low-risk patients. If there is not timely control of fungal infections and associated fever, the disease will continue to worsen, resulting in physical dysfunction or death. Patient concerns: Recurrent fever continued for 1 month in a young adult. Diagnoses and interventions: Non-albicans Candida (NAC) species probably was the main pathogen in this case based on the resolution of fever after capsofungin administration. Outcomes: The fever and the associated indicators, including white blood cell count, C-reaction protein, erythrocyte sedimentation rate, and BDG levels, showed improvement quickly. The patient left the hospital successfully after 18 days of caspofungin treatment. There was no recurrent fever at a follow-up of 1 year. Lessons: Clinicians should be aware that the incidence of fungal infection is increasing in low-risk patients. The BDG assay is still an effective tool used to diagnose invasive fungal diseases. Caspofungin is an effective drug for the treatment of some unknown fungal infections.